Analisis Forecasting Penjualan Obat Dengan Menggunakan Metode Least Square (Studi Kasus Pada Klinik King Medika Pelibaler) - Elisabeth Arnorce; Henrikus Herdi; Konstantinus Pati Sanga (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This study aims to determine the forecast of drug sales at King Medika Pelibaler Clinic in 2023-2027. This type of research is qualitative research. The type of data used is secondary data, namely data on drug sales results in 2018-2022 where data collection is carried out through documentation studies. Data analysis was carried out through Quantitative Descriptive analysis using the least square method to calculate and analyze drug sales forecasts at King Medika Pelibaler Clinic. The results of the data analysis obtained the equation y = Rp96,221,838 + Rp68,634,550x + Rp6,921,621x2. From this equation, it is obtained that the forecast of sales results for 2023 is IDR 364,420,077, in 2024 is IDR 481,505,974, in 2025 is IDR 612,435,113, in 2026 is IDR 757,207,494, and in 2027 is IDR 915,823,117, with a percentage of sales growth of 42%. The conclusion of the data analysis above states that the use of the least square method can be used to predict drug sales using drug sales data in the previous period.